2016
DOI: 10.1039/c6cp01723a
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic interactions of single crystalline organolead halide perovskites studied by Raman spectroscopy

Abstract: Organolead halide perovskites exhibit superior photoelectric properties, which have given rise to the perovskite-based solar cells whose power conversion efficiency has rapidly reached above 20% in the past few years. However, perovskite-based solar cells have also encountered problems such as current-voltage hysteresis and degradation under practical working conditions. Yet investigations into the intrinsic chemical nature of the perovskite material and its role on the performance of the solar cells are relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 47 publications
6
82
0
Order By: Relevance
“…4(b) . The rotation mode of the MA + in MAPbBr 3 single crystal can be weakened when the Br atom is gradually replaced with a Cl atom due to the higher electronegativity strengthens of the Cl − 49 . In this study, the rotation mode of the MA + was entirely restricted when Br was completely substituted by Cl.…”
Section: Resultsmentioning
confidence: 99%
“…4(b) . The rotation mode of the MA + in MAPbBr 3 single crystal can be weakened when the Br atom is gradually replaced with a Cl atom due to the higher electronegativity strengthens of the Cl − 49 . In this study, the rotation mode of the MA + was entirely restricted when Br was completely substituted by Cl.…”
Section: Resultsmentioning
confidence: 99%
“…Sharpa nd strong Raman bandsa t3 25, 970, 1480, 1586, and 2970 cm À1 can be attributed to CH 3 ÀNH 3 + in CH 3 NH 3 PbBr 3 . [21] With PA and APTES used as capping ligands, new bands at 890, 1178,a nd 1250cm À1 can be attributed to the PÀOs tretch, P=Os tretch, and POÀHs tretcho ft he PA ligands,r espectively. [22] Meanwhile, the bands at 1144, 1424, and 2940 cm À1 are attributed to the SiÀOÀSi stretch, SiÀCH 3 stretch, and NH 3 + stretch of the APTES ligands, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Jin et al has demonstrated that a strong electrostatic attraction between Cl and MA + is beneficial for chemical stability and recombination kinetics. 42,43 Furthermore, we measured the J-V characteristics in the dark and in forward direction for triple and triple_Cl devices ( Figure S12). The lower leakage current in the exponential region and lower slope in the high forward bias region for triple_Cl further confirms the lower recombination losses and R S .…”
Section: Methodsmentioning
confidence: 99%